Distribution and abundance of leptocephali in the western South Pacific region during two large-scale sampling surveys. (August 2022) - Miller, Michael J.; Shimizu, Madoka; Aoyama, Jun; Watanabe, Shun; Kuroki, Mari; Feunteun, Eric; Higuchi, Takatoshi; Takeuchi, Aya; Han, Yu-San; Sasal, Pierre; Dupuy, Christine; Jellyman, Donald; et al.
Highlights: 2 different-season surveys for leptocephali were conducted in the southwest Pacific. Mesopelagic larvae were abundant, shallow-water eel larvae were diverse in the west. Anguillids and probably conger eels spawned in the South Equatorial Current. The Chesterfield Is.–New Caledonia area was diverse for shallow water eel larvae. S. Pacific hydrographic structure varied latitudinally with west and east currents. Abstract: Although juvenile anguillid eels live in freshwater/estuarine habitats, and marine eels live in diverse ocean environments ranging from shallow-to-deep continental shelf areas and around islands to deep-benthic habitats and deeper meso- and bathy- pelagic zones, the larvae (leptocephali) of all species mix together in the ocean surface layer. All types of eel habitats are present in the western South Pacific (WSP), so it is a unique region for studying long-lived leptocephali, especially because the westward flowing South Equatorial Current (SEC) and several countercurrents pass through many different WSP island groups and deep waters where both anguillid and marine eels live and spawn. Large mouth-opening IKMT sampling surveys for leptocephali were conducted in the southwest Pacific extending to French Polynesia in Jan-Mar 2013 (99 tows, 78 stations, 1052 larvae) and Jul-Sept 2016 (187 tows, 111 stations, 3976 larvae) that collected about 152 species of 18 anguilliform and elopomorph families. The larvae of mesopelagic serrivomerid eels were the most abundant taxa in all oceanic areas, and they were particularly abundant at northern SEC or equatorial latitudes. Australian and New Zealand anguillid eels had spawned in the western SEC areas, as previously detected, and the larvae of tropical anguillids were also only caught in western areas. The larvae of the mesopelagic nemichthyid and derichthyid eels were also widely distributed at lower abundances and with more patchy distributions, but larvae of Eurypharyngidae, Cyematidae, and Monognathidae were rare. Shallow-water eel larvae were most abundant west of New Caledonia near the banks of the Chesterfield Islands, or near other island-groups, but they were rare in the 2 easternmost 2016 transects passing by both sides of Tahiti. Some conger eels were suggested to have spawned in offshore areas in the western region. Congrid Ariosoma and various shallow-water or slope eels had spawned in the region near the Chesterfield Islands or near New Caledonia where current jets can transport larvae westward, and eastward countercurrents exist. Some taxa of larvae of coastal species (muraenesocids, and elopomorphs) were extremely rare, all non-mesopelagic eel larvae were rare in the far-eastern transects, but the New Caledonia region with large shelf areas appears to be a high biodiversity region for marine eels, as it is for reef/shore fish in general.